Copper retention influenced by an invasive and a native plant in riparian soil - Jellian Jamin; Verena C. Schreiner; Katherine Muñoz; Herrmann F. Jungkunst; Gabriele E. Schaumann; Doerte Diehl (Environmental Advances, 2023)
Riparian soils are exposed to diverse anthropogenic stressors via aquatic pathways. Our study focuses on the impact of the invasive plant Impatiens glandulifera (Himalayan Balm) on processes that affect the filter and retention function of soils for copper, a regionally applied fungicide.Two soils, overgrown with the invasive I. glandulifera and by the native Urtica dioica were characterized for general soil properties and their copper retention ability assessed by a sequential extraction after seven days flooding with three different copper concentrations.We observed higher values for the absolute copper concentration in all fractions for the soil overgrown with I. glandulifera than for the soil overgrown with U. dioica. However, with respect to the total content, copper was more mobile in soil overgrown with U. dioica despite a higher organic matter content. The lower extraction recovery of the U. dioica soil suggests that more copper was mobilized in colloids which in long-term are easier washed out while I. glandulifera favors immobilization of organically chelated copper enhancing a legacy effect.Our results highlight the plant specific impact possibly induced by root exudates and plant residues affecting soil organic matter quality including the colloidal fraction and thus filter and retention functions of riparian soils.